Optimal Foreign Borrowing Strategies with Operations in Forward Exchange Markets - Folks, William R. (Journal of Financial and Quantitative Analysis, 1978)
When a unit of a multinational corporation requires short-term funding, it normally has the opportunity to obtain funds from a number of different sources, both internal and external to the country where these funds will be deployed. The possibility exists for borrowing in a currency other than the local currency of the borrowing unit. The purpose of this paper is to find the optimal currency source or sources for such a loan, when the borrowing unit can enter the forward exchange market for a term equivalent to the time to maturity of the loan.